Islamic Values in the United States - Ahmad Yousif (International Institute of Islamic Thought, 1993)
In this book, Haddad and Lurrunis present a scientific analysis of the social and religious values of the Muslim community in North America. The book probes into this community's psyche in an effort to detennine how its members, as a religious minority, cope or fail to cope with particular tenets of their religion while living in a non-Islamic environment. A number of problems and issues are encountered by this minority: marriage, divorce, interest, diet, pets, American holidays, and the roles of the masque and the imam. The authors attempt to determine the existence of correlations between such variables as length of time in the United States, the extent of dining with non-Muslims, gender, country of origin, and the subject's response to different values. The data was collected ftom numerous interviews and over three hundred questionnaires at Islamic tenters on the east coast, upstate New York, and the midwest.' Despite acknowledging the controversy surrounding the term "American Islam," the authors conclude that this phenomenon does exist in more than one form, depending on nationality, ethnic affiliation, level of education, economic status, and other factors. The findings also show that there are two dynamic, but opposing, scenarios occurring among Muslims in the United States ...